EVALUASI PROGRAM BANTUAN BST KEMENSOS (BANTUAN SOSIAL TUNAI KEMENTERIAN SOSIAL) TERHADAP PENINGKATAN KESEJAHTERAAN MASYARAKAT (DI DESA LOBUK) PADA ERA PANDEMI COVID-19 - Debby Mayang Lestari; Dina Kurniawati (Journal MISSY (Management and Business Strategy), 2021)
Human resources have a very important meaning in an organization, this is because human resources has an active and dominant role from humans in various organizational activities. Where humans have a role as determinants, actors and planners in achieving organizational goals and at the same time determining the progress of an institution. Both economic institutions such as companies or even government institutions, such as the government in the village. The purpose of this study is to explain the realization of the Ministry of Social's Cash Assistance and to know how to analyze the evaluation of the RI Ministry of Social Affairs' BST on improving the welfare of the Lobuk community. The data analysis technique uses Data Reduction, Data Presentation, Conclusions and Verification. After the researchers conducted interviews and observations about how the Ministry of Social's Bst Evaluation of the improvement of Community Welfare in the Covid-19 Pandemic Era can be drawn, the focus of the discussion is that Improving Community Welfare has indicators that become benchmarks assessment, one of which is the level of People's Purchasing Power. This situation makes the community have to return to changing spending patterns resulting from the covid-19 pandemic so that they can balance between income and household expenses, so that the BST assistance from the government only helps a little when compared to the monthly expenditure of the community before the pandemic, especially in the sector. fisheries seen from the results of interviews and observations that researchers did.